Increasing vulnerability of an endemic Mediterranean-climate conifer to changing climate and fire regime - Davis, Frank W.; Parkinson, Anne-Marie; Moritz, Max A.; Park, Isaac W.; D’Antonio, Carla M. (Frontiers in Forests and Global Change, 2025)
Conifer species of Mediterranean-type ecosystems (MTEs) are especially sensitive to coupled changes in climate and fire regime. Recently California’s MTE conifers have experienced elevated mortality, range shifts, and decreased abundance relative to broadleaf trees. Restricted-range species may be especially vulnerable to environmental change and are a high priority for climate change assessment and adaptation management. We used species distribution modeling and wildfire probability models to assess the potential vulnerability of Pseudotsuga macrocarpa (Bigcone Douglas fir, hereafter BDF), a restricted-range conifer of southern California mountains that is a species of concern because of its ecological importance and recent mortality due to drought and wildfire. We also modeled the distribution of Quercus chrysolepis (CLO), a widespread oak that can be co-dominant with BDF and that can limit fire spread and reduce crown fire risk to BDF compared to the risk from surrounding chaparral vegetation. Ensembles of MAXENT and General Boosted Models were produced for a 2.1 million ha model domain encompassing BDF’s 672,000 ha range for the period 1981–2010, and were projected to 2040–2069 and 2070–2099 using three climate models (warmer-wetter, warmer, and hotter-drier) under a high emission scenario (IPCC 5th Assessment, RCP 8.5). Wildfire projections were analyzed only for mid-century based on warmer-wetter and hotter-drier climate scenarios. Our analysis contributes several important new insights: (1) topoclimatic habitat for BDF could shrink by 19–57% by mid-century, especially for southernmost populations; (2) by mid-century, wildfire probability could increase 2–4 fold in BDF habitat, potentially diminishing the value of mid-to-high elevation sites as topoclimatic refugia; (3) CLO could play a diminishing role in providing refuge from severe wildfires as soon as mid-century but especially by end-of-century; (4) extensive areas of stable mid-century and late-century habitat are confined to national forests in the San Gabriel Mountains and Transverse Ranges. The climate and fire vulnerability of BDF could be reduced by management actions such as mechanical fuel treatments and post-fire restoration, but these are highly constrained by topography, access, and sensitive wildlife species. Our case study illustrates the rapidly increasing vulnerability of endemic conifer species in MTE forests.